2020
DOI: 10.1177/2055207620918715
|View full text |Cite
|
Sign up to set email alerts
|

Weighing the odds: Assessing underdiagnosis of adult obesity via electronic medical record problem list omissions

Abstract: Background: Obesity is a continuing national epidemic, and the condition can have a physical, psychological, as well as social impact on one's well-being. Consequently, it is critical to diagnose and document obesity accurately in the patient's electronic medical record (EMR), so that the information can be used and shared to improve clinical decision making and health communication and, in turn, the patient's prognosis. It is therefore worthwhile identifying the various factors that play a role in documenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…Furthermore, recognition and coding for obesity in civilian healthcare settings are poor [15]. Previous studies have shown that among patients who met the objective criteria for obesity, few were diagnosed with an obesity code [15,22,23] or clinical visits lacked a complete height and weight record to facilitate calculating BMI [15]. Additionally, another study showed that patients with known comorbidities (e.g., type 2 diabetes, hypertension, sleep apnea,) were not diagnosed with obesity [15,21].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recognition and coding for obesity in civilian healthcare settings are poor [15]. Previous studies have shown that among patients who met the objective criteria for obesity, few were diagnosed with an obesity code [15,22,23] or clinical visits lacked a complete height and weight record to facilitate calculating BMI [15]. Additionally, another study showed that patients with known comorbidities (e.g., type 2 diabetes, hypertension, sleep apnea,) were not diagnosed with obesity [15,21].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, recognition and coding for obesity in civilian healthcare settings are poor [15]. Previous studies have shown that among patients who met the objective criteria for obesity, few were diagnosed with an obesity code [15,23,24] or their clinical visits lacked a complete height and weight record to facilitate calculating BMI [15]. Additionally, another study showed that patients with known comorbidities (e.g., type 2 diabetes, hypertension, sleep apnea) were not diagnosed with obesity [15,22].…”
Section: Discussionmentioning
confidence: 99%
“…One way to overcome these barriers would be for a patient’s current health care provider to discuss benefits and risks of bariatric surgery with their eligible patients. However, previous studies have shown that clinicians seldom raise the issue of obesity with their patients (25); often, obesity is not even documented in the medical record (26,27). The findings in the present study paint a similar picture; less than 10% of potentially eligible patients had even a single discussion of bariatric surgery with their clinicians over 12 months, and less than 4% had multiple discussions.…”
Section: Discussionmentioning
confidence: 99%